PROPOSED BUSINESS STRATEGY FOR SHUTTLE BUS TO COMPETE WITH THE JAKARTA-BANDUNG HIGH-SPEED TRAIN BY EMPHASIZING THE FACTORS THAT AFFECT TRAVEL BEHAVIOR (STUDY CASE: CITITRANS) - Adiya Septianugraha, Prima
The introduction of the high-speed train (HST) "Whoosh" between Jakarta and Bandung poses a formidable challenge to existing shuttle bus services, notably Cititrans Shuttle. This thesis explores a strategic response to mitigate the impact of Whoosh on Cititrans' market share and operational viability. We conducted data analysis using a mixed-methods approach, combining quantitative surveys and qualitative interviews, using Pearson correlation and multiple regressions through IBM SPSS. The findings underscore the direct competition between Cititrans and Whoosh, with a notable shift in customer preference towards the latter. Customer segmentation analysis revealed two distinct groups: time-conscious travelers and leisure travelers. Furthermore, factors such as accessibility, availability, duration, and comfort emerged as critical influences on shuttle bus usage over HST. We formulated strategic recommendations from comprehensive analyses, primarily focusing on expanding pick-up and drop-off points to reach underserved populations. While this study provides valuable insights, it is not without limitations. Future research endeavors should aim to increase the sample size and incorporate additional variables for a more nuanced understanding. We recommend a broader competition analysis beyond Cititrans and Whoosh to fully capture the full spectrum of market dynamics influencing customer behavior in the transportation sector